90 anos de Problemas da criação de Dostoiévski (1929-2019): o texto em seu e em nosso tempo - Grillo, Sheila Vieira de Camargo; Brait, Beth; Pistori, Maria Helena Cruz; Lopes-Duganani, Bruna; Philippov, Renata (Bakhtiniana. Revista de Estudos do Discurso, 2021)
Editorial 16.2